Podoba ženske v Trubarjevih besedilih - Mileva Blažič, Milena (Slavia Centralis, 2020)
The Image of a Woman in Trubar's Texts. Trubar’s work was not fiction because his time was not a time of fiction-writing, but rather a time of non-fiction; nevertheless, his writings have literary qualities too. In his writings, especially the Catechism with the two explications from 1575, we often find the topics of children, women, family, and love. He also mentioned the notion of play and toys. These are proof of his new era conception of the child, woman, family and love. His literary heritage started in the 16th century and took its course simultaneously with the European period of Humanism, the Renaissance, and the European Reformation.
Keywords: Trubar; woman; image; virgin; widow; mother; love; beauty